Bacterial expression of the p24 gag protein of the bovine leukaemia virus - Zajac, V; Sláviková, K; Reinerová, M (Folia biologica, 1989)
The possibility of expression of the gag gene of bovine leukaemia virus (BLV) in the bacterial system was investigated. The DNA fragment coding for the gag core 24 kDa protein of BLV was inserted into the pORF1 expression vector. The polypeptides expressed in E. coli were analysed by Western blotting. The bacterially synthesized antigens were detected by the serum of a BLV-infected cow and by mouse monoclonal antibodies against the native p24 gag protein.
Keywords: rekombinantní DNA; DNA, Recombinant; monoklonální protilátky; Electrophoresis, Polyacrylamide Gel; Leukemia Virus, Bovine; Peptides; Antibodies, Monoclonal; Blotting, Western; virus bovinní leukemie; virové proteiny; Escherichia coli; Genes, Bacterial; western blotting; elektroforéza v polyakrylamidovém gelu; Viral Proteins; Retroviridae; bakteriální geny; peptidy